Illiberal Politics in Europe: Ideology, Policies, and Impact - Zsolt Enyedi; Petra Guasti; Dean Schafer; Bálint Mikola (Politics and Governance, 2025)
Our thematic issue focuses on the ideological and discursive foundations, policy outputs, and institutional impact of illiberal parties in Europe. The contributions highlight how illiberal actors reshape democratic institutions, popular attitudes, cultural narratives, and welfare policies. They also consider how illiberal ideas spread through mainstream political discourse. Crucially, the issue explores both the diversity of illiberal ideologies and the mechanisms of democratic resilience. Together, these studies show that illiberalism is not merely a rhetorical style but a substantive challenge to liberal democracy that operates through institutional changes, policy, and discourse.